Asri Jewellery's Online Marketing During the Covid 19 Pandemic in Tampaksiring Village, Gianyar - Ida Ayu Nyoman Yuliastuti; Putu Kepramareni; Anak Agung Putu Wiwik Sugiantari; I Ketut Sudipta Giri; I Gede Cahyadi Putra (AIBPM Publisher, 2021)
This study was carried out at Asri Jewellery engaged in a craft of bone carving, located at Br. Mantring, Tampaksiring Village, Bali. The training, mentoring, and evaluation methods for the sustainability of service activities. The results were the installation of wifi and neon boxes, website creation, product catalogs and brochures, business cards and business stamps, and online promotion assistance and through social media and marketplaces. The activities that have been carried out have provided the benefit of increasing a wider market share which resulted in the income maintained during the COVID-19 pandemic.